Peningkatan Pengetahuan Gizi Remaja Awal melalui Program Edukasi di SMP Gubahan Islam Tanjung Balai - Yusri, Imelda; Sari, Hayatur Ridha; Tambunan, Lili Yuliana (Jurnal Masyarakat Indonesia (Jumas), 2025)
Nutritional issues in adolescents are a crucial issue because during this period, physical growth and psychological development accelerate, requiring optimal nutritional intake. However, low nutritional knowledge among adolescents is often the primary cause of undernutrition or overnutrition. This study aimed to determine the effectiveness of nutritional health education on improving early adolescents' knowledge about meeting nutritional needs at Gubahan Islam Junior High School, Tanjung Balai, in 2025. The method used in this study was a pre-experimental study with a one-group pre-test and post-test design. The subjects were 40 seventh-grade students of Gubahan Islam Junior High School, Tanjung Balai, selected using a purposive sampling technique. Data were collected through questionnaires before and after the education. Data were analyzed using a paired t-test to determine differences in knowledge levels before and after the intervention. The results showed a significant increase in student knowledge after the nutrition education, with the average post-test score being higher than the pre-test (p < 0.05). This demonstrates that nutrition education is effective in improving adolescents' understanding of the importance of a balanced diet. In conclusion, nutritional health counseling is an effective educational method for increasing early adolescents' knowledge of nutritional needs. Such educational activities should be conducted regularly and sustainably to encourage healthy lifestyles from school age.